استراتيجيات المواجهة و علاقتها بالإحتراق النفسي لدى امهات أطفال الشلل الحركي الدماغي - وافي, ضاوية (كلية العلوم الاجتماعية لجامعة مستغانم, 2024)
تهدف هذه الدراسة إلى الكشف عن مدى تأثر استراتيجيات المواجهة بمستوى الاحتراق النفسي لدى أمهات أطفال الشلل الحركي الدماغي المتكفل بهم داخل جمعية التحدي لاطفال التوحد ببلدية بوقيرات، ولاية مستغانم، باستخدام المنهج العيادي ودراسة الحالة، والاعتماد على أدوات جمع البيانات المتمثلة في : الملاحظة العيادية، المقابلة العيادية نصف الموجهة، مقياس استراتيجيات المواجهة لبولهان واخرون، ومقياس الاحتراق النفسي لماسلاش،حيث إشتملت دراستنا على حالتين نفس الجنس ، وتوصلنا إلى النتائج التالية: - تتاثر استراتيجيات المواجهة التي تستعملها أمهات أطفال الشلل الحركي الدماغي بمستوى الاحتراق النفسي الوالدي لديهن . - يوجد مستوى مرتفع من الاحتراق النفسي لدى أمهات أطفال الشلل الحركي الدماغي. - تعتمد أمهات أطفال الشلل الحركي الدماغي على استراتيجيات المواجهة المركزة على الانفعال واستراتيجات المواجهة المركزة حول المشكل.
دراسة عيادية لحالتين مستغانم
This study aims to reveal the extent to which coping strategies are affected by the level of psychological burnout in the mothers of cerebral palsy children sponsored by them within the Challenge Society for Autism Children in the municipality of Boguirat, Mostaganem State, using the clinic curriculum and case study, and drawing on the data collection tools of: The clinical observation, the half-oriented clinical interview, the measure of Polhan and others' coping strategies, and the psychological burnout measure of Maslash, where our study included two same-sex cases (females), and we reached the following results: • Coping strategies used by mothers of cerebral palsy children are affected by their level of parental psychological burnout. • There is a high level of psychological burnout in mothers of cerebral palsy children. • Mothers of cerebral paralysis children rely on emotion-focused coping strategies and problem-focused coping strategies.
Keywords: استراتيجيات المواجهة، الاحتراق النفسي الوالدي، أمهات أطفال الشلل الدماغي.: coping strategies, parental psychological combustion, mothers of cerebral palsy children.